Flight and Migration from Africa to Europe Contributions of Psychology and Social Work - Groterath, Angelika; LANGHER, Viviana; Marinelli, Giorgia (Verlag Barbara Budrich, 2020)
This publication collects contributions to understanding and addressing migration flows from Africa to Europe and supporting social coexistence in the destination countries. Written by experts in psychology and social work, the articles approach the topic of immigration based on empirical research in their academic and professional specialties. The book focuses on issues of intervention, letting the research be the starting point for further plans. This focus makes the book valuable for professionals as well as policy makers.